Intelligence and Security Oversight - Richardson, Sophie. author. aut Link
IX, 134 p.
Keywords: This book presents a comprehensive source document on intelligence and security oversight and review. It compares the oversight arrangements found in nine countries—New Zealand, Australia, Canada, United States, United Kingdom, Germany, Netherlands, Norway and South Africa. This is done through an analysis of a wide range of areas including statutory basis, agencies overseen, membership, tenure, appointment/dismissal, mandate, powers, access to classified information, complaints function, reporting and, in the case of parliamentary committees, the frequency of meetings. Within an annotated bibliography section Richardson and Gilmour also provide detailed summaries of other relevant research and commentary aligned with oversight and review practices. Intelligence and Security Oversight: An Annotated Bibliography and Comparative Analysis comprehensively demonstrates the powers and limitations placed with, and on, oversight bodies, appealing to academics, researchers and practitioners in the intelligence and security environment.